Reduction of X-ray-induced DNA damage in normal human cells treated with the PrC-210 radioprotector - Brand, Michael; Sommer, Matthias; Jermusek, Frank; Fahl, William E.; Uder, Michael (Biology Open, 2018)
The aim of our study was to determine the protective efficacy of the PrC-210 aminothiol radioprotector against X-ray-induced DNA damage in normal human cells and to establish dose- and time-effect models for future PrC-210 use in humans. The PrC-210 structure has a branched structure which enables scavenging of reactive oxygen species (ROS) away from DNA. Normal human blood lymphocytes, fibroblasts and naked genomic DNA were exposed to PrC-210 seconds to hours prior to irradiation. Biological (γ-H2AX foci), chemical (8-oxo-deoxyguanosine) and physical (genomic DNA electrophoretic migration) DNA damage endpoints were scored to determine the ability of PrC-210 to suppress radiation-induced DNA damage. X-ray-induced γ-H2AX foci in blood lymphocytes were reduced by 80% after irradiation with 10, 50 and 100 mGy, and DNA double-strand breaks in fibroblasts were reduced by 60% after irradiation with 20 Gy. Additionally, we observed a reduction of 8-oxo-deoxyguanosine (an ROS-mediated, DNA damage marker) in human genomic DNA to background in a PrC-210 dose-dependent manner. PrC-210 also eliminated radiation-induced cell death in colony formation assays after irradiation with 1 Gy. The protective efficacy of PrC-210 in each of these assay systems supports its development as a radioprotector for humans in multiple radiation exposure settings.
EVALuna2:36109